Epicardial adipose tissue volume is an independent predictor of left ventricular reverse remodeling in patients with non-ischemic cardiomyopathy. (1st June 2022) - Yamaguchi, Yumi; Shibata, Atsushi; Yoshida, Toshitake; Tanihata, Akiko; Hayashi, Hiroya; Kitada, Ryoko; Ehara, Shoichi; Izumiya, Yasuhiro; Fukuda, Daiju
Abstract: Background: In some patients with non-ischemic cardiomyopathy, left ventricular (LV) contraction is improved by optimal medical therapy, leading to LV reverse remodeling (RR). Patients with heart failure with improved ejection fraction and LVRR have a good prognosis, but the factors that predict RR are not fully understood. The relationship between body composition and cardiovascular disease has been reported. The present study aimed to assess the clinical predictors of LVRR in association with body composition. Methods: We recruited patients who were diagnosed with non-ischemic cardiomyopathy between September 2017 and January 2020. Finally, 89 patients with a reduced LV ejection fraction were enrolled in this prospective study. Body composition, including ectopic fat, was measured in all patients using computed tomography. Echocardiography was performed 6 months after enrollment to evaluate LVRR. Results: LVRR was observed in 39 patients (43.8%) after 6 months. In terms of the demographic findings, epicardial adipose tissue volume was greater in the LVRR group than in the non-LVRR group (135.2 cm 3 [SD 128.4 cm 3 ] vs. 88.9 cm 3 [SD 54.6 cm 3 ]; p = 0.040). The Kaplan–Meier analysis demonstrated that adverse cardiac events were significantly less frequent in the LVRR group than in the non-LVRR group (log-rank test, p = 0.013). The multivariate logistic regression analysis identified epicardial adipose tissue volume as an independent predictor of LVRR (odds ratio [OR]: 1.010, 95% confidence interval [CI]: 1.001–1.01; p = 0.036). Conclusion: Epicardial adipose tissue volume is an independent predictor of LVRR in patients with non-ischemic cardiomyopathy. Highlights: Patients with improved left ventricular ejection fraction have a better prognosis. The higher the EAT volume, the more likely LV reverse remodeling will occur in patients with non-ischemic cardiomyopathy. A decrease in EAT volume in patients with reduced cardiac function means that the stage of heart failure is already advanced.